Application of Occupational Safety And Health To The Construction Project of A Building For Indonesian Migrant Workers In Penang, Malaysia - Agung Wahyudi Biantoro; RB Abdul Majid; D Vidayanti; A Hidayat; S Hidayat; Z Citra (International Journal Of Community Service, 2025)
The increase in workplace accidents among migrant workers in Pinang, Malaysia, is alarming, with reports indicating a significant rise in injuries, particularly in the construction sector. The low implementation of Occupational Health and Safety (K3) standards contributes to this issue, as many workers lack adequate training and face unsafe working conditions, leading to higher risks of accidents. Many migrant workers do not receive sufficient Occupational Health and Safety (K3) training before starting their jobs, leaving them unaware of potential hazards and safety protocols. The construction sector often exposes workers to hazardous environments, including inadequate personal protective equipment (PPE) and non-compliance with safety standards. Through community service efforts by a team of Civil Engineering lecturers from Universitas Mercu Buana, who possess expertise and OHS certification, it is hoped that a safer and healthier working environment will be created for Indonesian migrant workers in Pinang, Malaysia. After the outreach and training sessions, a total of 21 participants (construction workers) shared their opinions about the PKM KLN activity, in which they rated the level of expectation (importance) at 77% and performance (satisfaction) at 81%.